(untitled) (Journal of actual problems of jurisprudence, 2018)
This scientific article considers the legal problems of interrogation of victims and witnesses, as well as their effectiveness in criminal proceedings. Also, given the content of the concepts of victim and witness, features and differences questioning victims and witnesses. In addition, individuals safety issues involved in the criminal process in the manufacture of interrogation are raised. Article describes the successful interrogation of victims and witnesses, and hence the importance for the case received indications that depends on the skillful selection and skillful, effective application of the developed theory and practice tactical interrogation techniques. Thus, this article also covers the basics of production efficiency and witnesses questioning victims in court. And the victim is offered a tactic of interrogation and witnesses in court. Key words: interrogation, victim, witness, minor, features.